Digital Literacy in EFL Academic Writing: Students’ Perceptions and Practices - Nabila, Sorayya Veny; Wardani, Happy Kusuma (PROJECT (Professional Journal of English Education), 2026)
Digital literacy has become an essential competence for English as a Foreign Language (EFL) students, particularly in academic writing activities that increasingly rely on digital tools and online resources. This study aims to explore English Department students’ perceptions of digital literacy in academic writing at Universitas Qomaruddin. A mixed-methods approach with an explanatory sequential design was employed. Quantitative data were collected through a questionnaire consisting of 42 items distributed across seven digital literacy indicators. Semi-structured interviews were conducted to support and deepen the questionnaire findings as qualitative data. The participants were 47 English Language Education students aged between 19 and 25 years, drawn from three academic intakes (2022, 2023, and 2024).  They were selected using purposive sampling, as they had either completed or were currently enrolled in the Academic Writing course. The results indicate that students generally perceive digital literacy as beneficial for supporting academic writing, particularly in idea development, information evaluation, collaboration, and communication with peers and instructors. Although students demonstrated awareness of ethical writing practices, limited practical use of plagiarism-detection tools, and uneven confidence in advanced digital tools were evident.